The performance competencies needed to teach physical education from the point of view of physical education teachers in Mafraq Governorate (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to identify the performance competencies possessed by the physicaleducation teacher from the point of view of physical education teachers, identifyingthe differences in the estimates of physical education teachers for the performancecompetencies necessary for physical education teachers due to the variable of genderand years of experience. The researcher used descriptive approach, the sample of thisstudy consisted of (272) physical education teachers in Mafraq Governorate, theresearcher used questionnaire tool, The results of the study were as follows: Theperformance competencies possessed by the physical education teacher from the pointof view of physical education teachers were high for:the tool as a whole, the field of good planning for teaching, the field of lessonimplementation, the field of Control and assessment